Amniotic Membrane Graft and Hysteroscopic Adhesiolysis as Treatment for Asherman Syndrome Case - Rusly, Dewi Karlina; Ritonga, Mulyanusa Amarullah; Rachmawati, Anita; Rinaldi, Andi; Djuwantono, Tono (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Secondary amenorrhea which caused by intrauterine adhesions is called Asherman’s syndrome. This occurs when the uterine cavity becomes partially or completely blocked, which can damage the basal layer of the endometrium and cause the formation of adhesive cicatricial tissue. The prevalence or incidence of Asherman Syndrome ranges from 2.84-5.5% in women. Case Report: A woman 33 years old had a history of amenorrhea for 2 years and three times curettage due to miscariage. Ultrasound findings showed 1.35 cm long cicatrix in the uterine cavity, and probe had only entered 3 cm. The patient underwent hysteroscopy adhesiolysis and grafting of intrauterine amniotic membrane. The intrauterine catheter was monitored for 1 month. Postoperatively the patient also received estradiol valerate therapy 3 x 2 mg for three months. Management of Asherman syndrome with hysteroscopy adhesiolysis with direct observation accompanied by grafting of amniotic membrane using intrauterine catheter tube is one of the techniques to overcome recurrent intrauterine adhesion. Conclusion:  Secondary amenorrhea in Asherman syndrome is better treated operatively with direct observation of the hysteroscopy and adhesiolysis. The using of amniotic membrane graft and supportive therapy are very helpful for the success of endometrial growth and preventing recurrent adhesions, increase the menstrual volume and chances of pregnancy.Pencangkokan Selaput Ketuban dan Histeroskopi Adhesiolisis sebagai Penatalaksanaan untuk Kasus Sindrom AshermanAbstrakPendahuluan: Amenorea sekunder yang disebabkan oleh perlengketan intrauterin disebut sindrom Asherman dengan prevalensi berkisar antara 2,84 - 5,5%.Laporan Kasus: Seorang wanita berusia 33 tahun mempunyai riwayat amenore 2 tahun dan kuretase sebanyak 3 kali akibat abortus. Temuan USG menunjukkan cicatrix sepanjang 1,35 cm di rongga rahim, sondage hanya masuk 3cm. Pasien menjalani histeroskopi adhesiolisis dan pemasangan cangkok selaput ketuban intrauterin. Kateter intrauterin dipantau selama 1 bulan. Pascaoperasi pasien juga mendapat terapi estradiol valerat 3 x 2mg selama tiga bulan. Penatalaksanaan sindrom Asherman dengan histeroskopi adhesiolisis dengan observasi langsung disertai pemasangan cangkok selaput ketuban menggunakan selang kateter intrauterin merupakan salah satu teknik yang efekstif untuk mengatasi adhesiolisis intrauterin berulang.Kesimpulan: Amenore sekunder pada sindrom Asherman lebih baik ditangani secara operatif dengan observasi langsung berupa histeroskopi dan adhesiolisis. Pemasangan cangkok selaput ketuban dan terapi suportif sangat membantu keberhasilan pertumbuhan endometrium dan mencegah perlengketan berulang, meningkatkan volume darah saat menstruasi dan peluang terjadinya pembuahan.Kata kunci: Adhesi intrauterin, Histeroskopi, Pencangkokan selaput ketuban, Rekonstruksi endometrium, Sindrom Asherman.